Operations management : sustainability and supply chain management - Heizer, Jay.; Render, Barry; Munson, Chuck (Pearson, Boston, 2017)
In this book, we present a state-of-the-art view of the operations function.
Introduction to operations management -- Operations and productivity -- Project management -- Forecasting -- Designing operations -- Design of goods and services -- Managing quality -- Process strategy -- Location strategies -- Layout strategies -- Human resources, job design and work measurement -- Managing operations -- Supply chain management -- Inventory management -- Aggregate planning and S&OP -- Material requirement planning (MRP) and ERP -- Short-term scheduling -- Lean operations -- Maintenance and reliability -- Business analytics modules -- Decision-making tools -- Linear programming -- Transportation models -- Waiting-line models -- Learning curves -- Simulation
Includes bibliographical references and index.
Keywords: OPERATION MANAGEMENT; PRODUCTION MANAGEMENT